Influence of high flux hemodialysis on microinflammatory and nutritional status of uremic patients - LIU Na; ZHOU Lu; DING Kun; CHEN Ren-gui; ZHAO Wen-qi; YE Ting; SU Dong-dong (Linchuang shenzangbing zazhi)
Objective To investigate the influence of high flux hemodialysis（HFHD）on microinflam-matory and nutritional status of uremic patients. Methods 155 cases of uremic patients in our hospital from January 2013 to June 2015 were randomly divided into two groups: 82 cases of uremic patients with uremic treated by HFHD were selected into observation group,and 73 cases of uremic patients with uremic treated by hemodiafiltration + hemoperfusion（ HDF + HP） in the same period were selected into control group.Before and 12 months after the treatment,blood samples of 155 patients in each group were taken to detect the indicators of hypersensitive C-reactive protein（ hs-CRP）,interleukin（ IL-6）,tumor necrosis factor（TNF-α）,triglycerides（ TC）,total cholesterol（ TC）,β2-microglobulin（ β2-MG）,serum creatinine（SCr）,serum phosphorus（Ph）,body mass index（BMI）,total protein（TP）,albumin（Alb）,and statistical analyzed. Results After treatment,hs-CRP、IL-6、TNF-α levels of two groups were significantly reduced,statistically difference（ P < 0. 05）,and hs-CRP、IL-6、TNF-α levels of observation group were significantly lower than control group,statistically difference（ P < 0. 05）. After treatment,TG,TC,β2-MG,SCr,Ph levels of two groups were significantly reduced,statistically difference（ P < 0. 05）,and TG,TC,β2-MG,Scr,Ph levels of observation group were significantly lower than control group,statistically difference（ P < 0. 05）. After BMI,TP,Alb levels of two groups were significantly increased,statistically difference（ P < 0. 05）,and BMI,TP,Alb levels of observation group were significantly higher than control group,statistically difference（ P < 0. 05）. Conclusions Compared with hemodiafiltration + hemoperfusion（HDF + HP）,high flux hemodialysis could effectively improve the microinflammatory,renal function and nutritional status of uremic patients.